Case Report: m.13513 G>A Mutation in a Chinese Patient With Both Leigh Syndrome and Wolff-Parkinson-White Syndrome - Jian-Min Liang; Jian-Min Liang; Cui-Juan Xin; Guang-Liang Wang; Xue-Mei Wu; Xue-Mei Wu (Frontiers Media S.A., 2021)
A number of causative mutations in mitochondrial and nuclear DNA have been identified for Leigh syndrome, a neurodegenerative encephalopathy, including m. 8993 T>G, m.8993 T>C, and m.3243A>G mutations in the MTATP6, MTATP6, and MT-TL1 genes, respectively, which have been reported in Leigh syndrome patients in China. The m.13513 G>A mutation has been described only a few times in the literature and not previously reported in China. Here we report the case of a 15-month-old boy who presented with ptosis and developmental delay and was diagnosed with Leigh syndrome and well as Wolff-Parkinson-White (WPW) syndrome. The m.13513 G>A mutation was found in DNA from blood. He was intubated due to respiratory failure and died at 23 months of age. The m.13513 G>A mutation in the ND5 gene of mitochondrial DNA is associated with Leigh syndrome and WPW syndrome; however, this is the first report of this mutation in a patient in China, highlighting the geographical and racial variability of Leigh syndrome.